Hypallage et incidence de l’adjectif épistémique dans les structures complexes en anglais contemporain - Gérard Melis (Anglophonia)
Our purpose in this paper is to discuss the incidence of epistemic adjectives such as «sure» in «The boat is sure to sink», where the syntactic subject is not the notional subject of the qualification contained in the predicate: referring to something inanimate, «the boat» cannot normally be qualified with the property «be sure» and, as a consequence, it is not seen as the «real subject» of the predicate. That raises a question of syntax: how come the syntactic subject is not the real notional subject of the predicate? This paper discusses and rejects the hypothesis that a constituent is moved to subject position («raising») so that it can correspond to the theme of the sentence. We analyse such structures as examples of transfer of properties («hypallage»), doubting whether it is really feasible to identify the «real» notional subject of the qualification. Our main thesis is that some semantic properties of such predicates as «be sure» or «be likely», as opposed to «be probable» or «be liable», make it possible for them to qualify the whole predicative relationship and/or one of its components. The initial syntactic question is thus posed in terms of lexical properties.